MAJAS PERBANDINGAN DAN PERTENTANGAN DALAM NOVEL SERIBU MALAM UNTUK MUHAMMAD - Tia Indriyana; Sisilya Saman Madeten; Patriantoro Patriantoro (Universitas Tanjungpura, 2019)
AbstractThe researcher choosed figure of speech of comparison and contradiction as the focus of the research since they are common in literary works. The researcher used different methods for the sake of data collecting and analysis. The purpose of the methods was to have systematic, factual, and accurate description of the fact, nature, and relation between the related problems. The problem of this research was the language style ofthe two types of figure of speech, the meaning of the language style of each figure of speech, and its implementation as a model in the learning at school. The result of the analysis of the using figure of speech comparison and contradiction in novel Seribu Malam untuk Muhammad revealed figure of speech of comparison such as metaphor, personification, depersonification, allegory, antithesis, pleonasm, periphrases, anticipation, correction are there. The figure of speech of contradiction was there such as hyperbole, litotes, oxymoron, satire, innuendo, paradox, climax, anti-climax, anastrophe and hypalase. The implementation was done to year-12 of Senior High School on the basic competence of 3.9 which is about analyzing the content as well as the linguistic features of novel. Keywords: Figure of Speech, Language Style, Novel Seribu Malam untuk Muhammad